CARD14‐associated papulosquamous eruption (CAPE) in a toddler responding to treatment with acitretin. Issue 4 (2nd June 2021) - Wong, Gabriel Hong Zhe; Chia, Shi Yun; Wei, Heming; Rafi'ee, Khadijah; Koh, Mark Jean Aan; Tan, Ene Choo
Abstract: CARD14‐associated papulosquamous eruption (CAPE) is a rare autosomal dominant dermatosis that presents classically in early childhood with clinical features of both psoriasis and pityriasis rubra pilaris (PRP). The disease is known to be refractory to topical and systemic therapies classically used for psoriasis, with the majority of reported cases requiring treatment with biologics, such as ustekinumab and secukinumab. We present a toddler with a clinical presentation consistent with CAPE and found to have a novel heterozygous variant of the CARD14 gene. She was refractory to treatment with topical emollients and topical corticosteroids, but responsive to oral acitretin.